RESILIENCE AMONG DRUG ABUSER UNDER TREATMENT PROGRAM IN DRUG REHABILITATION CENTER IN SURABAYA - Hernanto, Fauziah Fitri; Harsa, Agung Putri; Permana, Roby Aji (Journal of Vocational Nursing, 2020)
Introduction: Drug abuse is very dangerous because it disrupts the ability to thinking process. Drugs have three dangerous characteristics, namely, addiction, tolerance, and habituation that cause an addict to be compelled to continue using drugs or to try drugs again. A former drug addict is prone to experience inability to pass through stress and stress due to symptoms of neurological dysfunction, physical craving suggestions, and loss of support from the environment. To deal with this situation, former drug addicts must defend themselves by bringing up a source of strength from within themselves called resilience. Increased self-resilience will help former drug addicts to cope with the difficulties experienced, times of crisis, avoid addiction, and overcome stress triggers. Methods: This study used a descriptive design and the sample size was 30 respondents with purposive sampling. The variables of this study was resilience measured through the questionnaire. Results: The results of descriptive analysis show that 16 (53.3%) respondents have low resilience, 6 (20%) respondents have very low resilience, and 8 (26.7%) respondents have sufficient resilience. Conclusion: The conclusion of this study is that most former drug addicts have low resilience. Health workers and facilitators play an important role in fostering the resilience of former drug addicts.